Community Motivation to Carry Out an Independent Business for Simple Processing of Zircon Sand (Puya) Mining Waste in Kurun Village - Enita Prentina; Saiffullah Darlan; Kusnida Indrajaya (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This research aims to determine the community's motivation to carry out an independent business in simple processing of zircon sand mining waste (puya) in Kurun village. The research was conducted using a naturalistic qualitative approach so that it could provide relevant information according to the research objectives. Data collection techniques include observation, interviews and documentation. The research subjects and informants consisted of zircon sand (puya) miners, the neighborhood head of the research location and collectors/buyers of clean puya. Data analysis was carried out simultaneously starting from: 1) data collection, 2) data reduction, 3) data display, 4) verification and conclusions. The results of the research show that the motivation of workers who are research subjects is intrinsic because the motivation of workers to process the remaining zircon or puya sand mining waste into an independent business is their own desire, which is based on the narrative of each worker from the answers to questions asked in the interview. in this research, and community motivation can make this job or business a business opportunity for those who don't have a business and can become a side business